Generation of strong magnetic fields with a laser-driven coil. (4th July 2018) - Zhang, Zhe; Zhu, Baojun; Li, Yutong; Jiang, Weiman; Yuan, Dawei; Wei, Huigang; Liang, Guiyun; Wang, Feilu; Zhao, Gang; Zhong, Jiayong; Han, Bo; Hua, Neng; et al.
Abstract : As a promising new way to generate a controllable strong magnetic field, laser-driven magnetic coils have attracted interest in many research fields. In 2013, a kilotesla level magnetic field was achieved at the Gekko XII laser facility with a capacitor–coil target. A similar approach has been adopted in a number of laboratories, with a variety of targets of different shapes. The peak strength of the magnetic field varies from a few tesla to kilotesla, with different spatio-temporal ranges. The differences are determined by the target geometry and the parameters of the incident laser. Here we present a review of the results of recent experimental studies of laser-driven magnetic field generation, as well as a discussion of the diagnostic techniques required for such rapidly changing magnetic fields. As an extension of the magnetic field generation, some applications are discussed.